Penerapan Pembelajaran Berdiferensiasi Untuk Meningkatkan Hasil Belajar Sejarah Kelas X4 Di SMA Negeri 2 Kupang - Eduk, Helena Krista; Ndoen, Fransina A; Utomo, Susilo Setyo; Wisnuwardana, I Gede W (FLORESIENSIS, 2024)
The methods used were group discussion, question and answer sessions, and presentations. The type of research was Classroom Action Research (CAR). This research consisted of two cycles, each cycle consisting of two meetings and one test. The research procedure was carried out in four steps, including: 1. Planning stage 2. Implementation stage 3. Observation stage 4. Reflection stage. The results of this research show that the learning outcomes of students in class X4 at SMA Negeri 2 Kupang after the implementation of differentiated learning experienced an increase in cognitive abilities and increased learning activity because students were directly involved in the learning process. The findings of this research show that differentiated learning is an effective learning strategy to improve the learning outcomes of diverse students because differentiated learning adjusts learning to the needs and learning styles of students so that all students reach their maximum learning potential.